Poor overall quality of clinical practice guidelines for musculoskeletal pain: a systematic review. Issue 5 (25th November 2017) - Lin, Ivan; Wiles, Louise K; Waller, Robert; Goucke, Roger; Nagree, Yusuf; Gibberd, Michael; Straker, Leon; Maher, Christopher G; O'Sullivan, Peter P B
Abstract : Objectives: Undertake a systematic critical appraisal of contemporary clinical practice guidelines (CPGs) for common musculoskeletal (MSK) pain conditions: spinal (lumbar, thoracic and cervical), hip/knee (including osteoarthritis) and shoulder. Design: Systematic review of CPGs (PROSPERO number: CRD42016051653). Included CPGs were written in English, developed within the last 5 years, focused on adults and described development processes. Excluded CPGs were for: traumatic MSK pain, single modalities (eg, surgery), traditional healing/medicine, specific disease processes (eg, inflammatory arthropathies) or those that required payment. Data sources and method of appraisal: Four scientific databases (MEDLINE, Embase, CINAHL and Physiotherapy Evidence Database) and four guideline repositories. The Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument was used for critical appraisal. Results: 4664 records were identified, and 34 CPGs were included. Most were for osteoarthritis (n=12) or low back pain (n=11), most commonly from the USA (n=12). The mean overall AGREE II score was 45% (SD=19.7). Lowest mean domain scores were for applicability (26%, SD=19.5) and editorial independence (33%, SD=27.5). The highest score was for scope and purpose (72%, SD=14.3). Only 8 of 34 CPGS were high quality: for osteoarthritis (n=4), low back pain (n=2), neck (n=1) and shoulder pain (n=1).